2020
DOI: 10.30537/sjcms.v4i1.582
|View full text |Cite
|
Sign up to set email alerts
|

Average Index Modelling of Campus Safety and Walkability: The Case Study of University of Sindh

Abstract: A pedestrian-friendly area encourages the inhabitants to experience the place enjoyably on foot. A pedestrian's sense of comfort is defined by the environmental qualities that encourage walking. The city's environmental qualities also make them better for walking, encouraging both physical and social activities. This Study focuses on safety and walkability in the University of Sindh. According to a survey done by researchers at the University of Sindh, the important issue at the university is lacking pedestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The weather, beauty and safety of the neighborhood could be limiting or encouraging factors for people to walk and use sidewalks. The amount of light and brightness, completeness of sidewalks, green space, presence of the police and traffic crashes are among other influential built environment factors (Memon et al. , 2020; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weather, beauty and safety of the neighborhood could be limiting or encouraging factors for people to walk and use sidewalks. The amount of light and brightness, completeness of sidewalks, green space, presence of the police and traffic crashes are among other influential built environment factors (Memon et al. , 2020; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The weather, beauty and safety of the neighborhood could be limiting or encouraging factors for people to walk and use sidewalks. The amount of light and brightness, completeness of sidewalks, green space, presence of the police and traffic crashes are among other influential built environment factors (Memon et al, 2020;Wang et al, 2019;Suarez-Balcazar et al, 2020). Furthermore, when examining weight-related outcomes, it is essential to account for differences among age groups, races and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-specific factors are associated with the travelers' demographic and socioeconomic attributes, which include age, gender, educational level, occupation, employability, household size, monthly income, lifestyles, and social activities [42][43][44]. The involvement of monetary crises has demonstrated that adjustments in the travel patterns contrast in connection to the family income, the distance, and the mode choices.…”
Section: Influencing Factors Mode Choicementioning
confidence: 99%